Isolation and identification of Bacillus subtilus as) probiotic ) from intestinal microflora of common carp Cyprinus carpio L.: Jamal K.H. Al-Faragi and Sundus A.A. Alsaphar - Faragi, Jamal K.H. (The Iraqi Journal of Veterinary Medicine, 2012)
The presence of Bacillus species Were investigated in the intestine of 50 fish specimens common carp Cyprinus carpio weigh range between 1400-1500g in weigh were obtained from commercial farms in north of Baghdad through period of September to December 2010.The result revealed presence of gram positive, rod shape bacteria grow in the mesosphilic temperature range. The optimal temperature was 25-35C° facultative aerobes and produce catalase an enzyme. The bacterial antagonist activity was tested with fish culture pathogenic bacteria. The modified antagonistic method results showed that Bacillus subtilus could inhibit Aeromonas hydrophila after 24 hours. The highest level of antibacterial substances of this bacillus was produced in 48 hours. The aim of this study is to isolate and identify the Bacillus spp. and study its efficacy as probiotic against A. hydrophila in a fish culture.